Transient Computational Fluid Dynamics Modeling of Air-Water Two-Phase Flow for Elbows - Kukrer, Ergin; Eskin, Nurdil (Springer International Publishing Ag, 2024)
This study presents a computational fluid dynamics model investigation of the air-water multiphase flow in elbows, which can be commonly found in many practical applications. The computational model was developed in ANSYS Fluent. The Eulerian-Eulerian approach was used in modelling, which employs individual equations for each phase. Air is injected at a 30 l/min airflow rate to water through nozzles at 16 points placed at equal angles in the circumferential direction. The water flow rate is determined as 180 l/min at the inlet. The test section consists of a complete U-bend system, which is a combination of two horizontal to vertical (upward and downward) and one vertical 180-degree elbow. Our study not only provides a detailed presentation of the numerical modelling methods developed for this complex geometry elbow but also discusses the results obtained from the model. The results are presented for each phase regarding local void fraction and phase velocities. In addition to numerical studies, experimental works were carried out for validation. Computational results were compared with the experimental acquisitions, and the results were in good agreement. It is observed that the Eulerian approach gives reasonable results to predict the flow characteristics of air-water flow in elbows.
14th International Conference on Computational Heat and Mass Transfer (ICCHMT) -- SEP 04-08, 2024 -- Dusseldorf, GERMANY
Keywords: Air-Water; Two-Phase Flow; Computational Multiphase Flow; Elbows; Eulerian Model; Local Void Fraction